Tom Spurgeon and Michael Dean. We Told You So: Comics As Art. Seattle: Fantagraphics Books, 2016. - Rachel R. Miller (Studies in 20th & 21st Century Literature, 2017)
Review of Tom Spurgeon and Michael Dean. We Told You So: Comics As Art. Seattle: Fantagraphics Books, 2016.
Keywords: Comics studies; history; alternative comics; journalism